Cloning, purification, crystallization and preliminary X-ray analysis of the Burkholderia pseudomallei L1 ribosomal protein - Abd Aziz, Abd Ghani (International Union of Crystallography, 2012)
The gene encoding the L1 ribosomal protein from Burkholderia pseudomallei strain D286 has been cloned into the pETBLUE-1 vector system, overexpressed in Escherichia coli and purified. Crystals of the native protein were grown by the hanging-drop vapour-diffusion technique using PEG 3350 as a precipitant and diffracted to beyond 1.65 Å resolution. The crystals belonged to space group P2(1)2(1)2, with unit-cell parameters a = 53.6, b = 127.1, c = 31.8 Å and with a single molecule in the asymmetric unit.